Women Engineers in Malaysia - Tapsir, Siti Hamisah; Mohd. Noor, Norliza (The Institution of Engineers, Malaysia, 2005)
Traditionally the field of engineering had been male dominant, as women were perceived as not suitable to take up this mentally and physically challenging profession. Thus women’s participation in the work force was only confined to the non-technical profession such as teachers, nurses and administrators. However, due to the equal opportunity for both genders in education in Malaysia, the participation and contributions of women in engineering field in the last few decades are invaluable. This paper discussed the progress of women in engineering from tertiary education up to professional level in Malaysia. The 21st century women engineers are known to exploit their potentials in engineering field even if it is physically demanding such as working in oil platform for petroleum engineering.